Morphosyntactic Analysis on English Inflectional Affixes with Special Reference to The Jakarta Post - Tri Widari, Koming (Humanis, 2018)
This study is entitled Morphosyntactic Analysis on English Inflectional Affixes with Special Reference to The Jakarta Post. It is aimed at finding out the types of inflectional affixes and  explaining how the inflected words found in The Jakarta Post are represented in tree diagram. The data of this study were taken from 31 articles related to business in The Jakarta Post printed edition published on 14 th , 15 th , and 16 th of June 2017. Observation method was applied in this study for collecting data. Firstly, Articles about business were chosen. Secondly, the articles were read intensively one by one in order to find out the affixes occurring on the articles. Thirdly, every affix was marked and noted down. Lastly, those affixes were classified into inflectional affixes. The data were analyzed descriptively based on the theories of inflectional affixes proposed by Francis Katamba (1993) in his book entitled Morphology as the main theory and the theory of tree diagram by Quirk at al. (1985) in his book entitled A Comprehensive Grammar of the English Language  presented as supporting theory. Based on the analysis, suffixes found in the articles are the suffix –s in noun, the suffix –s in verb, the suffix –ed, the suffix –ing, the suffix –er, and the suffix –est .The suffix –s in noun and suffix –ed are the most frequent types that appearing in the data. The finding also shows that there are five syntactic functions found in the data; they are subject, predicate, object, complement, and adverbial. The inflected word as predicate appears more frequently than the other syntactic functions.